2014
DOI: 10.1007/s11896-014-9148-z
|View full text |Cite
|
Sign up to set email alerts
|

Police Officers’ Perceptions of their Reactions to Viewing Internet Child Exploitation Material

Abstract: The purpose of this paper is to extend prior research on the impact of working in the area of Internet Child Exploitation (ICE) investigation by exploring ICE investigators' perceptions of and reactions to viewing child exploitation material. A diverse sample of 32 ICE investigators across all nine Australian jurisdictions individually participated in anonymous in-depth interviews. Participants were asked to discuss their subjective experience of viewing ICE material and its effect on them and to describe a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 22 publications
5
56
0
9
Order By: Relevance
“…Social support was another important factor in LEP's well-being. This view is supported by research which found social support decreases STS symptoms in members of LE [27,28] and is concurred by other LEP's reports [6,8,9,14] and by psychological models of resilience [72,73]. For the LEP in this study, social support included the formal support offered by management and during therapy and informal peer support.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Social support was another important factor in LEP's well-being. This view is supported by research which found social support decreases STS symptoms in members of LE [27,28] and is concurred by other LEP's reports [6,8,9,14] and by psychological models of resilience [72,73]. For the LEP in this study, social support included the formal support offered by management and during therapy and informal peer support.…”
Section: Discussionsupporting
confidence: 81%
“…Depictions of violence, the victims' displays of emotions, features personally relevant to LEP, norm violations and the medium of the material strongly modulated LEP's affective responses. These factors were also reported by other members of LE exposed to distressing material [6][7][8][9][10]14] and are corroborated by empirical research [36][37][38][39][40][41][42][43][44][45], suggesting the results are generalizable. In line with previous research in law enforcement [6-10, 14, 46], LEP's initial reaction to this material was one of distress.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…shock, distress, sadness, powerlessness, guilt), the experience of unwanted and intrusive thoughts and memories of images viewed, altered behaviour towards partners and children, and increased cynicism and suspiciousness of others [46,42]. These studies highlight the need to ensure provision of effective supervision and support to staff working in these areas [42,43,47].…”
Section: Working Conditionsmentioning
confidence: 98%